Evaluation of star-up grants in Nordland - Nordland Research Institute (Norwegian Social Science Data Services, 2014)
Entrepreneurial grants is a tool Innovation Norway uses as contribution to the establishment of enterprises, value added and employment. Nordland Research Institute was commissioned by Innovation Norway Nordland to evaluate the entrepreneurial grants in Nordland. Innovation Norway wants the most effective use of entrepreneurial grants. The aim is that the grant will lead to lasting and profitable jobs. The purpose of the study can be summarized as follows: 1 Consider the effect of entrepreneurial grants through a record of the status of projects that have received support. 2 Contribute to the knowledge that makes the entrepreneurial grants more effective in helping the prospective entrepreneurs establish their own business or get closer to an establishment.